Sociologia militans (Szociológiai Szemle, 2024)
D. Gusti, alongside F. Znaniecki, is undoubtedly one of the most significant sociologists between the two World Wars in East-Central Europe. Not only did he found a school, but constructed a sociological system, what he called monograhpical sociology, as well. In my introductory paper, I aimed to summarize his thoughts by deconstructing the definition of the nation. In the first part of the paper I outlined the motivation-goal elements, which make it understandable why Gusti undertook to construe such a system. The application of philosophy, or more precisely, neo-Kantian philosophy and Wundtian voluntarism gives the theoretical and methodological basis of his sociological outlook. At the same time, his system involves a number of historically specific sociological systems and concepts (Spencer, Durkheim, Tönnies, Simmel), which turn his monist system, i. e. one emphasizing the act of will as dominant, into an eclectic one. By laying too much stress upon the notion of act, he gets close to a teleological sociology with the scheme of which, W(ill)+F(rame)=M(anifestation), he constructs a closed system capable of grasping the diverse layers and dimensions of the structures of social existence in their functionality. Gusti attempted to understand reality and the field not only as typical, but as a comprehensive structure with its smallest components. His attempt to do so led to too many research projects with their respective theories. Pluridiscplinary approach may be justified if sociology tries to contribute to the reform and modernize society, that is to the solution of the social, economic, political, cultural and educational problems. Gusti tries to fulfil his goal by setting up a new science, the science of the nation, which is a combination of the social sciences (economics, politics, ethics, pedagogy and sociology). The grandiosity of his project and the non-selective epistemological and methodological approach meant that he was not able to reach solutions even after twenty-five years of field research. In spite of this, the methods of Gusti’s sociology of the village are applied throughout the region.